Nitric oxide is involved in light-specific responses of tomato during germination under normal and osmotic stress conditions - Piterková, Jana; Luhová, Lenka; Hofman, Jakub; Turecková, Veronika; Novák, Ondrej; Petrivalsky, Marek; Fellner, Martin (Annals of botany, 2012)
BACKGROUND AND AIMS: Nitric oxide (NO) is involved in the signalling and regulation of plant growth and development and responses to biotic and abiotic stresses. The photoperiod-sensitive mutant 7B-1 in tomato (Solanum lycopersicum) showing abscisic acid (ABA) overproduction and blue light (BL)-specific tolerance to osmotic stress represents a valuable model to study the interaction between light, hormones and stress signalling. The role of NO as a regulator of seed germination and ABA-dependent responses to osmotic stress was explored in wild-type and 7B-1 tomato under white light (WL) and BL. METHODS: Germination data were obtained from the incubation of seeds on germinating media of different composition. Histochemical analysis of NO production in germinating seeds was performed by fluorescence microscopy using a cell-permeable NO probe, and endogenous ABA was analysed by mass spectrometry. KEY RESULTS: The NO donor S-nitrosoglutathione stimulated seed germination, whereas the NO scavenger 2-phenyl-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide (PTIO) had an inhibitory effect. Under WL in both genotypes, PTIO strongly suppressed germination stimulated by fluridone, an ABA inhibitor. The stimulatory effect of the NO donor was also observed under osmotic stress for 7B-1 seeds under WL and BL. Seed germination inhibited by osmotic stress was restored by fluridone under WL, but less so under BL, in both genotypes. This effect of fluridone was further modulated by the NO donor and NO scavenger, but only to a minor extent. Fluorescence microscopy using the cell-permeable NO probe DAF-FM DA (4-amino-5-methylamino-2',7'-difluorofluorescein diacetate) revealed a higher level of NO in stressed 7B-1 compared with wild-type seeds. CONCLUSIONS: As well as defective BL signalling, the differential NO-dependent responses of the 7B-1 mutant are probably associated with its high endogenous ABA concentration and related impact on hormonal cross-talk in germinating seeds. These data confirm that light-controlled seed germination and stress responses include NO-dependent signalling.
Keywords: Solanum lycopersicum; donory oxidu dusnatého; signální transdukce; fyziologický stres; Fluoresceins; Signal Transduction; Imidazoles; imidazoly; osmóza; světlo; Cyclic N-Oxides; Pyridones; Plant Growth Regulators; Models, Biological; mutace; oxid dusnatý; Nitric Oxide; regulace genové exprese u rostlin; S-Nitrosoglutathione; scavengery volných radikálů; Gene Expression Regulation, Plant; Light; Stress, Physiological; Free Radical Scavengers; Kinetics; Abscisic Acid; Seeds; regulátory růstu rostlin; Germination; fluoresceiny; biologické modely; pyridony; Osmosis; cyklické N-oxidy; Nitric Oxide Donors; kyselina abscisová; Mutation; klíčení; kinetika; semena rostlinná; S-nitrosoglutathion